Induction of apoptotic temperature in photothermal therapy under various heating conditions in multi-layered skin structure - Kim, Donghyuk; Kim, Hyunjung (International Journal of Molecular Sciences, 2021)
Recently, photothermal therapy has attracted attention as an alternative treatment to conventional surgical techniques because it does not lead to bleeding and patients quickly recover after treatment compared to incisional surgery. Photothermal therapy induces tumor cell death through an increase in the temperature using the photothermal effect, which converts light energy into thermal energy. This study was conducted to perform numerical analysis based on heat transfer to induce apoptosis of tumor tissue under various heating conditions in photothermal therapy. The Monte Carlo method was applied to evaluate a multi-layered skin structure containing squamous cell carcinoma. Tissue-equivalent phantom experiments verified the numerical model. Based on the effective apoptosis retention ratio, the numerical analysis results showed the quantitative correlation for the laser intensity, volume fraction of gold nanorods injected into the tumor, and cooling time. This study reveals optimal conditions for maximizing apoptosis within tumor tissue while minimizing thermal damage to surrounding tissues under various heating conditions. This approach may be useful as a standard treatment when performing photothermal therapy.
Keywords: Apoptosis; Gold; Humans; Lasers; Models, Theoretical; Nanotubes; Phantoms, Imaging; Photothermal Therapy; Skin; Skin Neoplasms; Temperature; Apoptosis; Heat transfer; Photothermal therapy; Squamous cell carcinoma; Thermal damage